* Your assessment is very important for improving the workof artificial intelligence, which forms the content of this project
Download 7 : Induction
Brouwer–Hilbert controversy wikipedia , lookup
Wiles's proof of Fermat's Last Theorem wikipedia , lookup
Functional decomposition wikipedia , lookup
Numerical continuation wikipedia , lookup
Abuse of notation wikipedia , lookup
Non-standard calculus wikipedia , lookup
Elementary algebra wikipedia , lookup
Large numbers wikipedia , lookup
Laws of Form wikipedia , lookup
Fundamental theorem of algebra wikipedia , lookup
Hyperreal number wikipedia , lookup
Elementary mathematics wikipedia , lookup
Induction • Induction is basically a method for proving theorems about the natural numbers. • The method is important in computing applications; it is closely related to recursion, and it is a useful tool if you are trying to establish that an algorithm is correct. • A proof by induction on nature numbers of a given statement (or formula) consists of two steps: • 1- ( base step) Prove that the statement is true when n=1 . • 2- ( Inductive step) Prove that if the statement is true for any particular value k , then it is also true for the next value of n=k+1 . Example (1) Prove by induction: 1 2 3 ... n n (n 1) 2 • Proof: • Base step: Let put n 1 , then 1 1(12 1) is true. • Inductive step: assume that the formula is true for a fixed arbitrary natural number k :that is 1 2 3 ... k k (k 1) 2 • (This assumption is called the inductive hypothesis) • We need to deduce from this assumption that the formula is also true when n k 1. The left-hand side of the formula is 1 2 3 ... k (k 1) Then by using the inductive hypothesis we get 1 2 3 ... k (k 1) k (k 1) k 1 2 k 1) 2 (k 1)(k 2) 2 (k 1) (k 1) 1 2 (k 1)( The last line is with k+1 in place of n. So, the formula is also true for k+1. n (n 1) 1 2 3 ... n Thus by induction, 2 for all natural numbers. Example (2) Prove by induction the following statement 2 22 23 ... 2n 2n 1 2 Proof: 11 2 2 2 is true. Base step : Let n = 1. Then: Inductive step: now, assume, for n = k, the statement is held; that is, 2 22 23 ... 2k 2k 1 2 We need to show that for n = k + 1, the formula is also true. 2 22 23 ... 2k 2k 1 2k 1 2 2k 1 2.2k 1 2 2( k 1) 1 2 . So the formula is true for n = k + 1 Example 3 : For any natural number n , n3 + 2n is divisible by 3. • Proof: Basis Step: If n = 1, then n3 + 2n = 13 + 2(1) = 3. So it is divisible by 3. • Inductive step: Assume that for an arbitrary natural number k, k3 + 2k is divisible by 3. • To prove this for k+1, ( k + 1 )3 + 2( k + 1 ) = ( k3 + 3k2 + 3k+ 1 ) + ( 2k+ 2 ) = ( k3 + 2k ) + ( 3k2 + 3k+ 3 ) = ( k3 + 2k ) + 3( k2 + k + 1 ) • which is divisible by 3, because ( k3 + 2k ) is divisible by 3 (by assumption) and 3( k2 + k + 1 ) is also divisible by 3. So, by the induction the given statement is true for all n. Example (4) Prove that 8n – 3n is divisible by 5. Proof • Base step : Let n = 1. Then the expression 8n – 3n evaluates to 81 – 31 = 5, which is clearly divisible by 5. • Inductive step: assume, for n = k, then 8k – 3k is divisible by 5. Let n = k + 1. Then: 8k+1 – 3k+1 = 8k+1 – 3×8k + 3×8k – 3k+1 = 8k(8 – 3) + 3(8k – 3k) = 8k(5) + 3(8k – 3k) • The first term 8k(5) is divisible by 5 and 3(8k – 3k) is also divisible by 5 (by assumption). then the entire expression, 8k(5) + 3(8k – 3k) = 8k+1 – 3k+1, must be divisible by 5. • Then, for n = k + 1, the statement holds. Thus for all n. Example (5) Prove that 5n – 1 is divisible by 4. Proof • Base step : Let n = 1. Then the expression 5n – 1 evaluates to 51 – 1 = 4, which is clearly divisible by 4. • Inductive step: assume, for n = k, then 5k – 1 is divisible by 4. 5k – 1 = q 4 Then 5k – 1 = 4q = 4q + 1 or Let n = k + 1. 5k+1 – 1 = (5k 5) –1 = [(4q +1) 5] – 1 = 5 4q + 5-1